# Multiply. A) (2xy^3)(9x^2y^5) B)(8a)(2a^3b)(0)

### 3 Answers | Add Yours

The result of (2xy^3)(9x^2y^5)

= 2*9*x*x^2*y^3*y^5

= 18*x^3*y^8

For (8a)(2a^3b)(0) as one of the terms is 0, the result is 0.

**The required products are (2xy^3)(9x^2y^5) = 18*x^3*y^8 and (8a)(2a^3b)(0) = 0**

A)Using the following exponential law yields:

`a^x*a^y = a^(x+y)`

Reasoning by analogy, yields:

`(2*x*y^3)*(9*x^2*y^5) = (2*9)*(x^(1+2))*(y^(3+5))`

`(2*x*y^3)*(9*x^2*y^5) = 18*x^3*y^8`

B) Since one factor is 0,you need to use zero product rule, such that:

`(8a)(2a^3b)(0) = 0`

**Hence, evaluating the multiplications, yields `A) ` **

`18*x^3*y^8, B) 0. `

(2xy^3)(9x^2y^5) B)(8a)(2a^3b)(0)

`(2xx x xx y^3)(9xx x^2 xx y^5) `

`2xx x xx y^3xx9xx x^2 xx y^5`

`2xx9xx x xx x^2xxy^2xxy^5 `

`18xx x^3xxy^8 `

`(8a)(2a^3b)(0) = 0` because anything multiplied by 0 is immediately 0